2012
DOI: 10.5380/ce.v17i1.26370
|View full text |Cite
|
Sign up to set email alerts
|

Percepções Sobre a Violência No Cenário De Uma Unidade De Saúde Da Família

Abstract: RESUMO:Objetivou-se conhecer o contexto da violência no cenário de uma Unidade de Saúde da Família do sul do Brasil. Trata-se de pesquisa qualitativa realizada em 2008 e na qual se utilizou para a coleta de dados a estimativa rápida participativa. Participaram 19 informantes-chave, sendo seis moradores líderes de comunidade, seis agentes comunitários de saúde e sete entre demais integrantes da equipe de saúde. Os dados foram submetidos à análise temática de conteúdo, produzindo-se três categorias: policiamento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
0
4
0
5
Order By: Relevance
“…Esta contribui não somente para redução dos níveis de violência, como também se coloca na posição de mediadora na construção de uma rede de apoio que identifique, integre, articule e promova ações capazes de acolher à mulher nas diversas situações (13) . Outro profissional em destaque no atendimento à mulher vítima de violência é o defensor público.…”
Section: Discussionunclassified
“…Esta contribui não somente para redução dos níveis de violência, como também se coloca na posição de mediadora na construção de uma rede de apoio que identifique, integre, articule e promova ações capazes de acolher à mulher nas diversas situações (13) . Outro profissional em destaque no atendimento à mulher vítima de violência é o defensor público.…”
Section: Discussionunclassified
“…5,22 A study carried out having PHC health professionals as subjects, pointed out that family violence is recognized by professionals as a way used by families to resolve conflicts, which demonstrates their naturalization. 22 Therefore, it is necessary to recognize the problem for the action strategies against domestic violence.…”
Section: In Everyday Life We Realize One's Ability To Kill the Other mentioning
confidence: 99%
“…Because the health care sector is a gateway for caring for the cases of violence, the scientific literature states that the sector is a privileged locus for identifying these situations. 13,23 The service functions within a network Much has been discussed about network care for the protection of adolescent victims of violence. In this context, the MH emphasizes the importance of organizing care networks on health in the Unified Health System (SUS), defining them as integrated structures for the provision of health actions and services, institutionalized by public policies from collectively planned work, and deepening of the interdependent relationships among the actors.…”
Section: The Service Is a Referencementioning
confidence: 99%
“…22 Several studies point to the existence of that lack of training, given the problem, identified as a challenge to be overcome, in order to allow them to offer to the victims and their families the necessary care that is compatible with the complexity of the cases. 23,29 The training of personnel has been considered a priority and is done using multidisciplinary approaches, involving workers in the health service network, seeking definitive solutions, not punctual ones, regardless of their area of expertise. University education, in their perception, is not enough for the acquisition of skills and sensitivity to the conduct of cases.…”
Section: Investment In Human Resourcesmentioning
confidence: 99%